The Impact of Social Media Campaign on Green Coffee Image at Instagram @BLACKPASSION.ID - Aditya Eka Putra; Lian Agustina Setiyaningsih; Fitria Setyaningrum; Sri Widayati (Jurnal Komunikasi Nusantara, 2022)
In recent years, the research on social media especially Instagram becomes gradually popular along with the upsurge of the developing number of users. This is an opportunity for companies to use social media as a campaign tool, specifically to build the image of a product through campaigns on social media. In this research, an evaluation of the impact of social media campaigns on the green coffee image is conducted on Instagram @blackpassion.id. In the study, researchers use a quantitative approach as a research methodology. There are two variables used in this study, the independent variable "the impact of social media campaign" (X), and the dependent variable "green coffee image" (Y). The studied population are followers of Instagram @blackpassion.id, 920 followers. In this study, researchers obtained a sample of 90 followers. Further the researchers use a simple linear regression analysis to analyze the data. The result shows that campaign messages delivered on Instagram @blackpassion.id can be well received by respondents. So that there is an impact of the campaign through social media. Abstrak Dalam beberapa tahun terakhir, penelitian tentang media sosial khususnya Instagram menjadi populer secara bertahap seiring dengan meningkatnya jumlah pengguna yang berkembang. Hal ini menjadi peluang bagi perusahaan untuk menggunakan media sosial sebagai alat kampanye, khususnya untuk membangun citra suatu produk melalui kampanye di media sosial. Dalam penelitian ini, evaluasi dampak kampanye media sosial terhadap citra kopi hijau dilakukan di Instagram @blackpassion.id. Dalam penelitian, peneliti menggunakan pendekatan kuantitatif sebagai metodologi penelitian. Ada dua variabel yang digunakan dalam penelitian ini, yaitu variabel bebas “dampak kampanye media sosial” (X), dan variabel terikat “citra kopi hijau” (Y). Populasi yang diteliti adalah followers Instagram @blackpassion.id sebanyak 920 followers. Dalam penelitian ini, peneliti memperoleh sampel sebanyak 90 follower. Selanjutnya peneliti menggunakan analisis regresi linier sederhana untuk menganalisis data. Hasil penelitian menunjukkan bahwa pesan kampanye yang disampaikan di Instagram @blackpassion.id dapat diterima dengan baik oleh responden. Sehingga ada dampak dari kampanye melalui media sosial.